Teacher preparation in Ireland : history, policy and future directions - O'Donoghue, T. A. 1953- (Emerald Publishing, 2017)
This study of teacher preparation policy and practice in Ireland from Independence in 1921 to the present, highlights, within an international context, the extent to which the focus of preparation moved from nation-building until 1967, when free second-level education was introduced, to one concerned with improving the country's human capital.
Keywords: Teachers -- Training of -- Ireland.; Teachers -- Training of -- Ireland -- History.; Ireland.; elektronické knihy; electronic books